CLINICAL CHARACTERISTICS OF DEBUT AND RISK FACTORS OF PEDIATRIC MULTIPLE SCLEROSIS - Валерий Иванович Ларькин; Игорь Иванович Ларькин; Татьяна Аркадьевна Морозова; Степан Евгеньевич Аполлонов (Мать и дитя в Кузбассе)
The aim of the research – to study the features of the clinical picture, MRI data of the brain and spinal cord, to identify predisposing factors for the onset of multiple sclerosis (MS) in children and adolescents.